DOES SUSTAINABILITY RATING REALLY MATTER? - Mutmainah, Siti; Prastiwi, Andri; Lestari, Sari (Faculty of Economics and Business University of Mataram, 2025)
The Asia Sustainability Reporting Rating (ASRRAT) aims to incentivize the adoption of sustainability practices. However, comparative studies on the economic performance of rated versus non-rated companies remain limited. Employing legitimacy theory, this study evaluates the financial performance of ASRRAT members and non-members. The population comprises companies listed on the IDX between 2020 and 2022. Financial data were sourced from the Bloomberg database. Utilizing purposive sampling, 527 firm-year observations were obtained (122 for ASRRAT members) and analyzed using an independent samples t-test. The findings indicate that ASRRAT membership has an influence on certain financial metrics, although its impact on overall financial performance is inconsistent. This raises critical questions regarding the efficacy of ASRRAT in fostering substantive sustainability practices beyond reputational objectives. The practical implications of this research suggest that companies should prioritize measurable sustainability actions with financial impact and that ASRRAT should develop outcome-based criteria correlated with financial performance. Sustainability plays a crucial role in balancing profitability, social well-being, and environmental conservation.